Education on the importance of health awareness - Indah Setyaningsih; Aan Kunaedi; Nawal Hilmy Anoez (Community Empowerment, 2021)
Efforts to reduce the number of Covid-19 cases on a daily basis can begin with simple things like developing the habit of properly hand washing. In addition, education about women's reproductive health is provided. This service is carried out at the Robbani Foundation which has 13 foster children. This service promotes a better understanding of proper hand washing techniques. This activity is expected to help reduce the spread of Covid-19 by cultivating clean living education and sharing with orphans and poor.